J.M.I. St. Cyr correspondence - St. Cyr, J. M. I. (John Mary Irenus), 1804-1883.
Two letters (1880 January 19 and 30) to John Wentworth in which St. Cyr describes his experiences as priest at the first Roman Catholic church in Chicago, Ill.
Typewritten transcripts.
Roman Catholic priest. Born in France; emigrated to the United States in 1831.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Wentworth, John, -- 1815-1888 -- Correspondence; Catholic Church -- Illinois -- Chicago -- History; Clergy